The implication of a diversity of non-neuronal cells in disorders affecting brain networks - Carrier, Micaël; Dolhan, Kira; Bobotis, Bianca Caroline; Desjardins, Michèle; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2022)
The central nervous system (CNS) neuron is classically considered the functional unit of the brain. Analysis of the physical connections and co-activation of neurons, referred to as structural and functional connectivity, respectively, is a conventional metric to understand their interplay at a higher level. A myriad of glial cell types throughout the brain composed of microglia, astrocytes and oligodendrocytes are key players in the maintenance and regulation of the neuronal network dynamic. Microglia are the central immune cells of the CNS able to affect neuronal populations in number and connectivity, allowing for maturation and plasticity of the CNS. Microglia and astrocytes are part of the neurovascular unit, and together they are essential to protect and supply nutrients to the CNS. Oligodendrocytes are known for their canonical role in axonal myelination, but also contribute, with microglia and astrocytes, to CNS energy metabolism. Glial cells can achieve this variety of roles because of their heterogeneous populations comprised of different states. The neuroglial relationship can be compromised in various manners in case of pathologies affecting development and plasticity of the CNS, but also consciousness and mood. This review covers structural and functional connectivity alterations in schizophrenia, major depressive disorder, and disorder of consciousness, as well as their correlation with vascular connectivity. These networks are further explored at the cellular scale by integrating the role of glial cells diversity across the CNS to explain how these networks are affected in pathology.